Long-term ageing behaviour of martensite in shape memory Cu-Al-Ni alloys - Aydogdu, A; Aydogdu, Y; Adiguzel, O (Elsevier Science Sa, 2004)
The behaviour of shape memory alloys, which exhibit a peculiar property, is evaluated by the structural changes in microscopic scale. Metastable beta phases of copper-based ternary alloys are very sensitive to the heat treatments and transform martensitically from the ordered structures to the long-period layered structures on cooling. Martensitic transformations in these alloys occur by two or more lattice invariant shears on a (001)(beta) plane of austenite matrix, which is basal plane or stacking plane of martensite. The basal plane of 9R (or 18R) type martensites originates from one of the (110)(beta) planes of the parent phase, and an homogenous shear occurs on the basal plane in either of two opposite directions during the transformation. The (001)(beta) type plane of parent phase is subjected to the hexagonal distortion with martensite formation on which atom sizes have important effect. In case the atoms occupying the lattice sites have the same size, the hexagon becomes regular hexagon; otherwise the hexagon undergoes a distortion in case atom sizes are different. In case atom sizes are equal, the interplane spacings become equal for each other of the particularly selected pairs of diffraction planes providing a special relation between miller indices, while they become different in the case of different atom sizes. Due to this property, the spacing differences between the selected pairs of diffraction planes reflect the degree of order in martensite. The change in this difference can be attributed to the interatomic changes with ageing in the material, and the decrease in spacing difference leads to disordering in martensite. In the present contribution, long-term ageing behaviour of the martensite in two shape memory Cu-Al-Ni alloys has been studied by X-ray measurements and electron microscopy. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: shape memory effect; martensite; ageing; layered structures; hexagonal distortion